(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
The study included the concept of the general budget and the factors affecting it, as well as the concept of the exchange rate and the factors affecting it. Data were used, through the Central Bank of Iraq for the period 2004-2023, and the results of the study were that there was a significant relationship between the two variables in the short term and the long term, through the integration program. Joint and Single Test – Equation cointegration.